ANALISIS SEKTOR UNGGULAN KABUPATEN LOMBOK UTARA TAHUN 2015 – 2019 - Ristawan, Rizal; Ulfah, Baiq Rizka Milania (Nusantara Hasana Journal, 2022)
This research is entitled "Analysis of the Leading Sector of North Lombok Regency in 2015 - 2019". The purpose of this study is to analyze the leading sectors and non-sector sectors in North Lombok Regency. The type of research in this research is descriptive research with a quantitative approach. The data collection technique was carried out by studying literature and the type of data used was secondary data. The data analysis technique uses the Location Quotient (LQ) method. The results of the study using the Location Qoutient (LQ) method, it was found that there are nine (9) leading sectors in North Lombok Regency which have an LQ value of more than one (> 1), the sectors are the agriculture, forestry and fisheries sector, electricity and gas procurement sector, Water Supply Sector, Waste Management, Waste and Recycling, Wholesale and Retail Trade Sector, Car and Motorcycle Repair Sector, Government Administration Sector, Defense and Mandatory Social Security, Real Estate Sector, Enterprise Services Sector, Education Services Sector, and Sector Other Services. Meanwhile, there are eight (8) non-leading sectors in North Lombok Regency which have an LQ value of less than one (<1) namely the Mining and Quarrying Sector, Manufacturing Sector, Construction Sector, Transportation and Warehousing Sector, Accommodation and Food and Drink Sector, Sector information and communication, financial and insurance services sector, health services sector and social activities.